Evaluating the quality of public governance: indicators, models and methodologies - Bovaird, Tony; Loffler, Elke (2003)
This article provides an overview for this special issue on the evaluation of the quality of public governance. It charts the move in the public sector during the 1990s from concern largely with excellence in service delivery to a concern for good governance. It examines what we mean by governance and `good governance' and the dimensions of `good public governance'. It demonstrates that there is now widespread interest in measuring not only the quality of services but also improvements in quality of life and improvements in governance processes. It discusses how measures of good governance are being used in different contexts around the world. Finally, it considers how the measurement of good governance can be encouraged, e.g. through awards, inspections, setting funding conditions and empowering stakeholders to demand better evidence. - Reproduced.
Keywords: Public administration; Good governance